A study protocol for determining the role of Sympathetic activity in Post-injury outcomes: Impact on sleep and caRdiovascular health InvesTigation (SPIRIT) - Lauren E. Walker; Sarah M. Jurick; Victoria Thomas; Thomas Arnold; Katerina Elisman; Sachi Kalra; Autumn Mains; Stephanie Rioux; Michael Galarneau; Cameron McCabe; Jason M. Lavender; Jacob Collen; et al. (PLoS ONE, 2025)
Introduction A growing body of research indicates that combat-injured service members are at heightened risk of a wide range of adverse physical and mental health outcomes. However, data on long-term health outcomes of United States (US) combat-injured service members remain limited, particularly in relation to cardiovascular outcomes and potential underlying mechanisms. The goal of the “determining the role of sympathetic activity in post-injury outcomes: impact on sleep and cardiovascular health investigation (SPIRIT)” study is to better understand the relationship between combat injury severity and cardiovascular function, sleep disorders, and mental health concerns among post-9/11 US combat casualties. Methods Here, we describe a remotely conducted, nationwide, cross-sectional study of 100 minimally injured (Injury Severity Score [ISS] ≤ 3) and 100 severely injured (ISS ≥ 14) post-9/11 US combat casualties. Injury and demographic data will be collected from both retrospective sources and the participants themselves. Participants will complete well-validated surveys electronically to assess mental health symptoms and sleep problems. Three wearable devices will be mailed to participants: (1) an ambulatory electrocardiogram (ECG) monitor for seven days of wear, (2) a Home Sleep Test (HST) device to be worn for one night, and (3) a 24-hour ambulatory blood pressure monitor to be worn for one day. Lastly, participants will visit a local laboratory to provide blood and urine samples for analysis. This protocol is registered on Clinicaltrials.gov under #NCT05971433. Results and conclusions This study will be among the first to remotely evaluate long-term physical and mental health outcomes in US combat casualties. This study aims to collect robust at-home ECG, sleep, and blood pressure data and examine the associations of combat injury severity with sleep disorders, mental health, cardiovascular risk, and sympathetic nervous system activation. Findings will help inform future research, such as interventional or subsequent longitudinal observational investigations of combat-injured veterans.